Luminescence: Full‐Color Tunable Circularly Polarized Luminescent Nanoassemblies of Achiral AIEgens in Confined Chiral Nanotubes (Adv. Mater. 19/2017). Issue 19 (May 2017) - Han, Jianlei; You, Jing; Li, Xianggao; Duan, Pengfei; Liu, Minghua
Abstract : Circularly polarized emissive nanotubes are fabricated by simple mixing of chiral gelator with achiral dyes, as described by Jing You, Pengfei Duan, Minghua Liu and co‐workers in article number1606503 . Various dyes are encapsulated into the chiral nanotubes, showing tunable emission color. Chirality transfer occurs from the confined chiral space of nanotubes to the guest dye aggregates. This method provides a simple and general approach for fabricating full‐color tunable circularly polarized emissive nanomaterials.